(untitled) (Proceedings OPTIMAL, 2026)
Pulmonary tuberculosis is an infectious disease that can be cured if treatment is carried out diligently. Pulmonary tuberculosis is caused by the bacterium Mycobacterium tuberculosis. It is a lower respiratory tract infection. Most bacteria enter the lung tissue through airborne infection and then undergo a process known as primary focus of Ghon. (2) Approximately 10 million people worldwide suffer from pulmonary tuberculosis. The three countries with the highest TB prevalence are India, China, and Indonesia. The 2018 Riskesdas research showed that the number of TB cases was estimated at around 845,000, with a mortality rate of 35 per 100,000 population. The purpose of this study was to determine the relationship between knowledge and motivation with adherence to taking anti-tuberculosis medication in pulmonary TB patients in the Klasaman Community Health Center Working Area of ​​Sorong City. Research Methods; This type of observational study is a quantitative study with a cross-sectional approach. This study aims to determine the relationship between the level of knowledge and motivation with adherence to taking anti-tuberculosis medication in pulmonary TB patients. The population of this study was all pulmonary TB patients undergoing treatment in the Klasaman Community Health Center working area totaling 32 cases, while the sample was carried out using a purposive sampling technique. Data collection techniques were by direct interviews and observation. Univariate analysis is a statistical technique that functions to describe the characteristics of each variable in the study. The test used in this bivariate analysis used the chi-square test. The results of the Chi-Square statistical test showed a p-value of 0.0317, indicating a significant relationship between knowledge and adherence to TB medication (p < 0.05). The results also showed a significant relationship between motivation and adherence to TB medication, with a p value of 0.0158 (p < 0.05). This means that a positive motivational attitude can influence adherence to TB medication in tuberculosis patients. Conclusion: Most respondents had good knowledge about preventing TB transmission, and a positive motivational attitude can influence adherence to TB medication in tuberculosis patients at the Klasaman Community Health Center in Sorong City.